Community seroprevalence of SARS-CoV-2 in children and adolescents in England, 2019–2021 - Ratcliffe, H; Tiley, KS; Andrews, N; Amirthalingam, G; Vichos, I; Morey, E; Douglas, NL; Marinou, S; Plested, E; Aley, P; Galiza, EP; Faust, SN; et al. (BMJ Publishing Group, 2022)
Objective: To understand community seroprevalence of SARS-CoV-2 in children and adolescents. This is vital to understanding the susceptibility of this cohort to COVID-19 and to inform public health policy for disease control such as immunisation. Design: We conducted a community-based cross-sectional seroprevalence study in participants aged 0–18 years old recruiting from seven regions in England between October 2019 and June 2021 and collecting extensive demographic and symptom data. Serum samples were tested for antibodies against SARS-CoV-2 spike and nucleocapsid proteins using Roche assays processed at UK Health Security Agency laboratories. Prevalence estimates were calculated for six time periods and were standardised by age group, ethnicity and National Health Service region. Results: Post-first wave (June–August 2020), the (anti-spike IgG) adjusted seroprevalence was 5.2%, varying from 0.9% (participants 10–14 years old) to 9.5% (participants 5–9 years old). By April–June 2021, this had increased to 19.9%, varying from 13.9% (participants 0–4 years old) to 32.7% (participants 15–18 years old). Minority ethnic groups had higher risk of SARS-CoV-2 seropositivity than white participants (OR 1.4, 95% CI 1.0 to 2.0), after adjusting for sex, age, region, time period, deprivation and urban/rural geography. In children <10 years, there were no symptoms or symptom clusters that reliably predicted seropositivity. Overall, 48% of seropositive participants with complete questionnaire data recalled no symptoms between February 2020 and their study visit. Conclusions: Approximately one-third of participants aged 15–18 years old had evidence of antibodies against SARS-CoV-2 prior to the introduction of widespread vaccination. These data demonstrate that ethnic background is independently associated with risk of SARS-CoV-2 infection in children. Trial registration number: NCT04061382.